2018
DOI: 10.1016/j.ebiom.2018.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts in macular fibrosis secondary to neovascular age-related macular degeneration - the potential sources and molecular cues for their recruitment and activation

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly in developed countries. Neovascular AMD (nAMD) accounts for 90% of AMD-related vision loss. Although intravitreal injection of VEGF inhibitors can improve vision in nAMD, approximately 1/3 of patients do not benefit from the therapy due to macular fibrosis. The molecular mechanism underlying the transition of the neovascular lesion to a fibrovascular phenotype remains unknown. Here we discussed the clinical features and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 90 publications
2
64
0
1
Order By: Relevance
“…In an experimental CNV model using irradiated mice engrafted with green fluorescent protein (GFP)-positive bone marrow cells, many of the α-SMA-positive cells were also GFP-positive suggesting a systemic source of mesenchymal cells in CNV lesions [201]. Macrophages may also give rise to myofibroblasts via macrophage-myofibroblast transition (MMT) in subretinal fibrosis secondary to nAMD [202]. Choroidal pericytes may represent another potential source of myofibroblast precursors where they have been found to infiltrate CNV and transdifferentiate into collagen I-expressing cells in a photocoagulation CNV mouse model [203].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…In an experimental CNV model using irradiated mice engrafted with green fluorescent protein (GFP)-positive bone marrow cells, many of the α-SMA-positive cells were also GFP-positive suggesting a systemic source of mesenchymal cells in CNV lesions [201]. Macrophages may also give rise to myofibroblasts via macrophage-myofibroblast transition (MMT) in subretinal fibrosis secondary to nAMD [202]. Choroidal pericytes may represent another potential source of myofibroblast precursors where they have been found to infiltrate CNV and transdifferentiate into collagen I-expressing cells in a photocoagulation CNV mouse model [203].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…It has been suggested that anti-VEGF therapy significantly improved vision and quality of life for patients with nAMD [11,12]. Nevertheless, about one-third of patients do not get effects from anti-VEGF therapy owing to macular fibrosis or atrophy [13]. In addition, there is a heavy demand for repeated intravitreal injections to maintain efficacy [14,15], which leads to a heavy economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…Die CNV bei nAMD verändert sich unter der Anti-VEGF-Therapie zu einer fibrosierten Läsion [14]. Die funktionellen Auswirkungen dieser fibrovaskulären Umwandlung, wie auch morphologische Veränderungen, sind individuell sehr unterschiedlich [15 -17].…”
Section: Diskussionunclassified